EKSISTENSI KEPOLISIAN DALAM PENUNTUTAN PERKARA TINDAK PIDANA RINGAN DIWILAYAH HUKUM POLRES LABUHANBATU - Dr. Iskandar Muda Sipayung (Universitas Labuhanbatu, 2021)
This study aims to analyze the legal aspects of the existence of the police in the prosecution of minor criminal cases in the Labuhanbatu District Police Legal Territory. This research is Normative Empirical, namely research by looking at the conditions in the field by linking the legal sources of the regulations in force in the Republic of Indonesia. The benefits that will be received from the results of this research are to find out and analyze the legal basis of the police's authority in prosecuting minor criminal cases and to find out and analyze the existence of the police in prosecuting minor criminal cases in the Labuhanbatu Police Legal Territory. The results of the study show that firstly, the Legal Basis of Police Authority in Prosecuting Minor Crime Cases is based on the provisions as stated in Article 205 of the Criminal Procedure Code. Second, the existence of Labuhanbatu Police Investigators has so far carried out their duties as stipulated in article 205 of the Criminal Procedure Code by acting as Public Prosecutors in cases of minor crimes.Keywords: Existence, Police, Minor Crime.